Времена года: [стихи] / С. Я. Маршак, С. В. Михалков, А. Л. Барто, В. Д. Берестов ; художник И. Цыганков - Цыганков Иван А. (Библиотека начальной школы, 2016)
Экземпляры: ф30 (20180521) / Инвентарный номер: 56078 / Цена: 107.92 / Сис.шифр: 84(0) / Авт.знак: В 81 / ГРНТИ: 17.82.93 / ББК: 84(0)